Frog, Baldr and Lemminkäinen : approaching the evolution of mythological narrative through the activating power of expression - Rédaction (Mondes normands médiévaux, 2014)
Frog, Baldr and Lemminkäinen : approaching the evolution of mythological narrative through the activating power of expression - a case study in Germanic and Finno-Karelian cultural contact and exchange, Thèse de doctorat soutenue en 2010, (University College London) Résumé : The orientation of this study is to explore what the sources for each narrative tradition can (and cannot) tell us about their respective histories, in order to reach a point at which it becomes possible to discuss a rela.